The significance of the canonical form of marriage = L’importance de la forme canonique du mariage = Il significato della forma canonica del matrimonio - Majer, Piotr (Philosophy & canon law, 2015)
The paper offers arguments for the canonical form of contracting marriage ad validitatem matrimonii which has been obligatory since the Council of Trent. Responding to critique and postulates for abolishing the obligatory character of the canonical form, the Author presents its stricte ecclesiastical significance. In the face of the secularization of marriage, the canonical form of contracting marriage should allow the Church not only to exercise church jurisdiction over the marriage, but, first of all, to be a tool of testimony about the sacramentality of marriage and the guarantee of authenticity of the matrimonial sign towards both the future spouses and, ad extra, the world.